Analisis kualitas pelayanan publik di bidang kesehatan - Thomas Ovin Toni; Ishviati J Koenti (Kajian Hasil Penelitian Hukum, 2019)
This research aims to determine the quality of public services in the health by conducting a case study of health services at Palue Health Center, analyzing constraints that hinder optimization of health services and offering solutions as an effort to resolve these problems so that health services in Palue Health Center can be optimal.The research is descriptive and empirical research, the approach method used is empirical juridical approach. The research is located in Palue Health Center, Palue District, Sikka Regency, East Nusa Tenggara Province. Primary data collection by observation and interview techniques, secondary by library research. The research result were analyzed by qualitative methods and presented descriptively. Public services in the health sector at Palue Health Center have not been optimal. This is based on 5 five basic health service requirements and 5 five public service indicators Parasuraman et al. and 4 four indicators of the fulfillment of the right to health. Constraints that cause health services are not optimal, among others, facilities and infrastructure that are inadequate, incomplete and damaged, lack of workforce, competency in human resources and community participation in appreciating services held by Palue Health Center and government policies that hamper improvement service quality. Efforts to optimize health service including improving and completing advice and infrastructure, to increase the competency of health and non-health workers in accordance with The Minimum Standard of Health Service in The District City and government policies that accommodate the fullfilment of the rights of Palue Health Center and remote and very remote areas based on applicable laws and regulations.